Advances in Meteoroid and Meteor Science - Trigo-Rodríguez, J. M (Springer, 2017)
"This volume is a compilation of articles that summarize the most recent results in meteor, meteoroid and related fields presented at the Meteoroid 2007 conference held at the impressive CosmoCaixa Science Museum in Barcelona, Spain. Researchers in meteor science and supporting fields representing more than 20 countries participated at this international conference." "The papers contained in this volume underwent the rigorous refereeing process, and they are good examples of the continuous progress being made in this research field. Technological advances in meteor and meteoroid detection, the ever-increasing sophistication of computer modeling, and the proliferation of autonomous monitoring stations continue to create new niches for exciting research on meteoroids and their parent bodies."--Jacket.